Influência da composição dos eletrodos na microestrutura de soldas em aço ARBL HARDOX 450 2021 - Conte, Paola (2021)
There are possible causes of failures that directly influence the quality and useful life of the material in welding that need to be taken into account in an analysis developed such as: knowing the main characteristics of the metal and the process to be used, consumables for welding between other factors. Therefore, understanding how the welding process influences the characterization of the microstructure is fundamental. This type of process is widely used in engineering companies and technology. The present work proposes the study of the GMAW welding process (MIG/MAG) automated machine applied to high-strength, low-alloy steel material Hardox 450. performed the welding on Hardox 450 steel with different deposition wires, analyzed the influence of the composition of the electrodes in the microstructure of the material, to determine which influences generate in the microstructure and microhardness of the metal. With laboratory analysis of metallography and microhardness that provided the data for the conclusions of this work, made it possible to see that the best result occurred with the filler metal ER90S-D2, where the microstructure had a more granulation refined and the hardness remained higher along the weld joint